The Role of Big Data Analytics in Strategic Human Resource Planning: A Framework for Organizational Decision-Making - Shanty Manik (Journal of Digital Informatics, 2025)
In today’s data-driven business environment, organizations face challenges in effectively utilizing Big Data Analytics (BDA) for Strategic Human Resource Planning (SHRP). While BDA has the potential to enhance HR decision-making, its application in strategic HR functions remains underexplored. This study aims to investigate the role of BDA in SHRP and its impact on organizational decision-making, particularly in recruitment, workforce planning, and employee retention. A quantitative research approach was adopted, employing a structured survey administered to 30 HR professionals across various industries. The study finds that BDA adoption positively influences HR decision-making effectiveness, with significant effects on recruitment efficiency and workforce planning, but a weaker impact on employee retention strategies. The study also develops a framework for integrating BDA into SHRP processes, offering a practical guide for HR professionals. By contributing empirical evidence to the theoretical understanding of BDA’s role in SHRP, this research enhances the existing literature on data-driven decision-making in HRM. The findings also provide valuable insights for organizations seeking to leverage BDA for more effective strategic HR practices, promoting a data-informed approach to workforce management.